(untitled) - Coombe, Christine; Davidson, Peter (New York;Cambridge, 2012)
This collection of original articles provides language teachers with a theoretical background of key issues associated with language testing as well as practical advice on how to improve the effectiveness of the tests they develop and implement. Written by internationally prominent researchers and educators, the chapters are organized into five sections: key issues in the field, assessment purposes and approaches, assessment of second language skills, technology in assessment, and administrative issues. Chapters assume no particular background knowledge and are written in an accessible style
Keywords: English language -- Study and teaching -- Foreign speakers; Second language acquisition -- Study and teaching; Ngôn ngữ Anh -- Dạy và học -- Người nước ngoài; Ngôn ngữ thứ hai -- Dạy và học